PENGARUH ABSENSI DAN METODE PEMBELAJARAN AKTIF TERHADAP HASIL BELAJAR EKONOMI PADA SISWA - Nuramaliah; Sandi; Syamsuria (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
ABSTRACT This study aims to determine the effect of attendance and active learning methods on the economic learning outcomes of grade X.1 students at SMA Negeri 25 Bone. Attendance and active learning methods are two critical factors presumed to influence student achievement. High absenteeism can reduce learning opportunities, while the implementation of active learning methods is believed to enhance student participation, motivation, and understanding during the instructional process. This research employs a quantitative approach with a pretest-posttest experimental design. The research subjects consisted of 29 students from class X. Data analysis results showed an increase in the average learning outcome score from a pretest of 53.68 to a posttest of 83.45. The results of the paired sample t-test showed a value of t = -14.274 with a p-value < 0.001, indicating that the difference is statistically significant. Consequently, it can be concluded that attendance and the application of active learning methods have a significant influence on improving students' economic learning outcomes. This study supports previous findings emphasizing the importance of active student engagement in learning to achieve optimal results.